Adapted physical activity and its role in improving body image to the visually impaired - عروسي الدراجي (sports creativity, 2025)
The current study aimed to determine the role of adapted sports activities in improving body image among visually impaired individuals. The descriptive approach was used, and the research sample consisted of 16 children (boys and girls) from the School for Visually Impaired Children in M'Sila. Nine of these children participated in adapted sports activities, while seven did not. The Body Image Scale developed by Dr. Samia Mohamed Saber Mohamed Abdel Nabi (2008), Professor of Mental Health at the Faculty of Education in Benha, was administered. The results showed statistically significant differences between visually impaired children participating in adapted sports activities and those not participating in them in the dimension of individual body perception, favoring the participants. Furthermore, statistically significant differences were found between visually impaired children participating in adapted sports activities and those not participating in them in the dimension of individual body perception through others, again favoring the participants. The results also indicated no statistically significant differences among visually impaired individuals participating in adapted sports activities attributable to gender.